2019
DOI: 10.1101/753178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell transcriptome analysis reveals an essential role for Gata2b in hematopoietic lineage decisions in zebrafish

Abstract: Hematopoietic stem cells (HSCs) are tightly controlled to maintain a balance between myeloid and lymphoid cell differentiation. Gata2 is a pivotal hematopoietic transcription factor required for HSC generation and maintenance. We generated a zebrafish mutant for the mouse Gata2 orthologue, gata2b. We found that in adult zebrafish, gata2b is required for both neutrophilic-and monocytic lineage differentiation. Single cell transcriptome analysis revealed that the myeloid defect present in Gata2b deficient zebraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
1
1
0
Order By: Relevance
“…Analysis of gata2a um 27 mutants shows a role for Gata2a during primitive myelopoiesis while analysis of gata2b u 5008 mutants show that Gata2b is dispensable for primitive myelopoiesis but is required for definitive myelopoiesis. This phenotype can be observed at 4 dpf and is consistent with decreased myeloid cells in the whole kidney marrow of adult Gata2b mutants ( Gioacchino et al, 2019 ). Butko et al (2015) showed using an elegant genetic switch experiment and gata2b derived promoter elements that the majority of adult myeloid cells are derived from gata2b + cells.…”
Section: Discussionsupporting
confidence: 75%
“…Analysis of gata2a um 27 mutants shows a role for Gata2a during primitive myelopoiesis while analysis of gata2b u 5008 mutants show that Gata2b is dispensable for primitive myelopoiesis but is required for definitive myelopoiesis. This phenotype can be observed at 4 dpf and is consistent with decreased myeloid cells in the whole kidney marrow of adult Gata2b mutants ( Gioacchino et al, 2019 ). Butko et al (2015) showed using an elegant genetic switch experiment and gata2b derived promoter elements that the majority of adult myeloid cells are derived from gata2b + cells.…”
Section: Discussionsupporting
confidence: 75%
“…gata2b mutants, on the other hand, present a reduction in HSC at the onset of definitive hematopoiesis and have defect in neutrphil and monocytic differentiation lineages as adults 40 . Surprisingly, there were no obvious hematopoietic defects in the adult gata2b -/-; gata2a -/fish, suggesting GATA2 is not required for hematopoiesis 34 .…”
Section: Discussionmentioning
confidence: 99%